HIGHER EDUCATION UNDER NATIONAL EDUCATIONAL POLICY (NEP) 2020: A TEACHER’S PERSPECTIVE STUDY - Sarita Kumari (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Education is the foundation stone of the nation as it plays a powerful role in the growth and development of the country and its citizens. One cannot deny the fact that education is a powerful tool and based on the recommendations by a panel headed by Dr Kasturi rangan former chairman of Indian space research former Indian Space Research Organization (ISRO), the New Education Policy has been drafted that focuses on equity, quality, affordability, and accountability of education in our country. This policy contributes directly to transforming India, that is Bharat, The vision of the Policy is to in still among the learners a deep-rooted pride in being Indian, not only in thought, but also in spirit, intellect, and deeds, as well as to develop knowledge, skills, values, and dispositions that support responsible commitment to human rights, sustainable development. In this paper, the author is going to explore the awareness and perception of university professors regarding structure of higher education, Multiple Exit and entry Option, Multidisciplinary Education, Vocational Education and Academic Bank of Credit, Common Entrance Exam, Online Education and Digital Education, Internationalization of Education Integrated B.ED. , Single regulatory body HECI and, awareness of all polices 1968, 86, and 2020.